Manual on standardized research techniques in coconut breeding - Santos, G.A.; Batugal, P.A.; Othman, A.; Baudouin, L.; Labouisse, Jean-Pierre; International Coconut Genetic Resources Network (1996)
This manual will enable coconut breeders and germplasm researchers worldwide to use standardized techniques as guidelines in breeding and germplasm conservation. It is hoped that this manual will help cooconut researchers to obtain better and comparable results to accelerate the development of improved varieties for millions of coconut farmers. Available from IPGRI Regional Office for Asia, the Pacific and Oceania In collaboration with the International Coconut Genetic Resources Network (COGENT)